Intervention for Creating Equal Classrooms - Пінчук , Катерина; Заліпська, Кристина (Київський національний університет імені Тараса Шевченка, 2021)
Bullying and victimization are prevalent during adolescence. In Europe and North America, approximately 6% of middle school students are bulling others, and approximately 10% of middle school students are bullied 2 or 3 times in a month. Moreover, adolescence is a sensitive period for social status. LaFontana and Cillessen (2009) showed a clear peak in prioritizing status enhancement in early adolescence. Given that the CEC (Creating Equal Classroom) project aims to reduce the level of bullying through mitigating classroom status hierarchy, grade 7 is a particularly relevant developmental stage to implement this intervention project.Target population: Adolescents from grade 7 at the middle schoolMethods: Questionnaires, multilevel modeling with Mplus 8.0 to estimate the intervention effects due to the nested nature of data, trainings and discussions.Short description of results and conclusions: Pupils are encouraged to take responsibility for their social environment and for interacting with peers. This program is effective in reducing the frequency of adolescents' involvement in bullying situations. With help of this program, the number of both initiators and victims of bullying will decrease.

Булінг і віктимізація поширені в підлітковому віці. У Європі та Північній Америці приблизно 6% учнів середніх шкіл знущаються над іншими, а приблизно 10% учнів середніх шкіл зазнають знущань 2 або 3 рази на місяць. Крім того, підлітковий вік є чутливим періодом для соціального статусу. LaFontana та Cillessen (2009) показали явний пік у пріоритеті підвищення статусу в ранньому підлітковому віці. Враховуючи, що проект CEC (Creating Equal Classroom) спрямований на зниження рівня булінгу через пом’якшення ієрархії статусу класу, 7 клас є особливо актуальним етапом розвитку для реалізації цього проекту інтервенції.Досліджувані: підлітки з 7 класу середньої школиМетоди: Анкети, багаторівневе моделювання з Mplus 8.0 для оцінки ефектів інтервенції через вкладений характер даних, тренінги та обговорення.Короткий опис результатів і висновки: учнів заохочують брати відповідальність за своє соціальне оточення та за взаємодію з однолітками. Ця програма ефективна для зниження частоти залучення підлітків до ситуацій булінгу. За допомогою цієї програми зменшиться кількість як ініціаторів, так і жертв булінгу.
Програма-інтервенція для створення рівноправних класів
Keywords: Булінг; рівність; учні 7 класу; віктимізація; Bullying; equality; pupils from 7th grade; victimization